Raising Students’ Awareness of a Healthy Lifestyle through Blogging - Varenko, T.K. (Xарків: ХНУ імені В.Н. Каразіна, 2017)
Without being taught to mind their health, unaware of the dangers behind the extensive use of and dependence on technology and machines, the humanity’s young generation is facing a future with too many health issues to lead a satisfying and productive life, to give birth to healthy children, to work and create. The aim of this paper is to demonstrate how blogging can be an effective way of making technology serve as both a deterrent to its excessive use and an advocate of a healthy lifestyle when introduced in higher education within the framework of health-related majors and courses.
Keywords: healthy lifestyle; blogging